Icons and the Liturgy, East and West : History, Theology, and Culture - Denysenko, Nicholas E. (Book collections on Project MUSE., 2017)
"Icons and the Liturgy, East and West: History, Theology, and Culture is a collection of nine essays developed from papers presented at the 2013 Huffington Ecumenical Institute's symposium "Icons and Images," the first of a three-part series on the history and future of liturgical arts in Catholic and Orthodox churches. Catholic and Orthodox scholars and practitioners gathered at Loyola Marymount University to present papers discussing the history, theology, ecclesiology, and hermeneutics of iconology, sacred art, and sacred space in the Orthodox and Catholic traditions. Nicholas Denysenko's book offers two significant contributions to the field of Eastern and Western Christian traditions: a critical assessment of the status of liturgical arts in postmodern Catholicism and Orthodoxy and an analysis of the continuity with tradition in creatively engaging the creation of sacred art and icons. The reader will travel to Rome, Byzantium, Armenia, and Chile, among other countries, to see how Christians of yesterday and today experience divine encounters through icons. Theologians and students of theology and religious studies, art historians, scholars of Eastern Christian Studies, and Catholic liturgists will find much to appreciate in these pages. Contributors: Nicholas Denysenko, Robert Taft, S.J., Thomas M. Lucas, S.J., Bissera V. Pentcheva, Kristin Noreen, Christina Maranci, Dorian Llywelyn, S.J., Michael Courey, Andriy Chirovsky"--